2023
DOI: 10.3390/molecules28155795
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Polyphenols Extraction from Wild Bilberry Leaves—Antimicrobial Properties and Stability Studies

Abstract: Polyphenolic extracts from natural sources have received great interest due to their beneficial properties for human health. A method to reduce their variability is to use the design of experiments which allows a limited number of experiments to be performed while exploring the experimental space. Firstly, a 23-full factorial model was used to investigate the polyphenols extraction from wild bilberry leaves. Spectrophotometric data (the content of polyphenols, flavonoids, chlorophyll and radical scavenger acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
(49 reference statements)
3
12
2
Order By: Relevance
“…Thus, the amounts of the four most abundant constituents of maceration, HAE, UAE, and MAE are either comparable to or higher than the amounts previously reported for some of the extracts studied [52][53][54][55][56][57]. For example, the content of chlorogenic acid (6.09-8.70%) in four different extracts prepared by maceration or ultrasound extraction (twigs and leaves from the Cindrel Mountains, Batrana Peak, Romania; extraction medium 50% ethanol) was comparable to the content in the macerate and UAE extracts studied in this work, in contrast to the content of quercetin 3-O-rutinoside (3.23-4.66%), which was up to 4-fold higher [52]. The UAE extract prepared via sonotrode (leaves from organic cultivation in Huelva, Spain; 30% ethanol) showed a higher content of chlorogenic acid (9.07%) compared to the UAE extract in this research, while quercetin 3-O-glucuronide was only present at 0.73% [53].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, the amounts of the four most abundant constituents of maceration, HAE, UAE, and MAE are either comparable to or higher than the amounts previously reported for some of the extracts studied [52][53][54][55][56][57]. For example, the content of chlorogenic acid (6.09-8.70%) in four different extracts prepared by maceration or ultrasound extraction (twigs and leaves from the Cindrel Mountains, Batrana Peak, Romania; extraction medium 50% ethanol) was comparable to the content in the macerate and UAE extracts studied in this work, in contrast to the content of quercetin 3-O-rutinoside (3.23-4.66%), which was up to 4-fold higher [52]. The UAE extract prepared via sonotrode (leaves from organic cultivation in Huelva, Spain; 30% ethanol) showed a higher content of chlorogenic acid (9.07%) compared to the UAE extract in this research, while quercetin 3-O-glucuronide was only present at 0.73% [53].…”
Section: Discussionsupporting
confidence: 76%
“…The structure of compound 29 was tentatively found as quercetin hydroxy-methylglutaryl deoxyhexoside due to its [M-H] − at m/z 591 and fragment ions signals at m/z 489, 447, and 301, where the ion at m/z 447 was probably obtained by the loss of 3-hydroxy-3-methylglutaroyl units from the deoxyhexose moiety and that at m/z 489 by cleaving from a 3-hydroxy-3-methylglutaroyl unit compared to the fragmentation pathway of quercetin-3-O-(4 ′′ -(3-hydroxy-3-methylglutaryl))-α-rhamnoside that had been previously identified in lingonberry fruit and leaves [65]. Flavonoids similar to 16, 17, 21, 23, and 29 were detected before in V. myrtillus leaves and/or stems [8,[52][53][54][55][56][57]66].…”
Section: Qualitative Lc-ms Analysis Of the Extractsmentioning
confidence: 81%
“…Our results showed that syringic acid was present in the highest concentration in the MAE extract, while caffeic acid was the predominant compound in the PLE extract. Değirmencioğlu et al [ 48 ] identified syringic acid as the most abundant compound in the leaves of bilberry from Turkey, Stefanescu et al [ 49 ] reported the predominance of feruloylquinic acid in extracts of wild bilberry from Romania, while Brezoiu et al [ 50 ] pointed out chlorogenic acid as the dominant compound in ethanolic bilberry extracts. The same authors identified caffeic acid only in hydroethanolic extracts, explaining its presence as a result of chlorogenic acid hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Bilberries have various health-promoting effects. Different research studies evidenced Antioxidants 2024, 13, 250 2 of 18 that fruits, leaves, and/or extracts exhibit beneficial effects such as antioxidant [3,4], antiobesity [5], anticarcinogenic [6], cardioprotective [7], anti-inflammatory, antimicrobial [3,8], hypoglycemic [9], and vision-improving effects [10]. Several clinical trials of metabolic disorders reported that bilberry consumption as fruits (frozen, processed, or fresh) or juices resulted in a remarkable decrease in inflammatory markers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, flavonoids (quercetin, myricetin), flavanols (catechin, epicatechin, procyanidins dimers, or trimers), stilbenoids (resveratrol), organic acids (shikimic, quinic, citric, and malic acids), phenolic acids, and hydroxycinnamic acid derivatives (p-coumaric, caffeic, ferulic acids) could also be found [15]. The main phytocompounds in leaf extracts are catechins (catechin, epicatechin, gallocatechin, epigallocatechins), cinchonains I and II, phenolic acids (mainly p-coumaric, chlorogenic, and caffeic acids), proanthocyanidins, and flavonols (quercetin, rutin, kaempferol, and their derivatives) [3,16].…”
Section: Introductionmentioning
confidence: 99%